Nanoplasmonic biosensors - Crulhas, Bruno P. [UNESP]; Basso, Caroline R. [UNESP]; Pedrosa, Valber A. [UNESP] (Taylor & Francis, 2017)
During the last decades, analytical science has provided new possibilities for getting chemical information about objects and systems. As a result, novel methodologies have been developed focusing on low cost, miniaturization, and simplification of existing techniques (Oliveira et al., 2008; Malhotra and Chaubey 2003). Analytical methods for identification and determination quantitative and qualitative properties of chemical and biological compounds are increasingly used in several areas of diagnosis, including diseases caused by viruses and bacteria, environmental monitoring, pathogen detection, antigen-antibody binding, detection of chemicals substances for defense and security systems (Grieshaber et al., 2008; Oliveira et al., 2008).